ANALISIS DAMPAK KEBIJAKAN PROGRAM KELUARGA HARAPAN TERHADAP KONSUMSI - Riyanto, Kusuma Arum; Ananda, Candra Fajri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The study aims to analyze the impact of the Family Hope Program (PKH) policy on household consumption during the COVID-19 pandemic. Using a quantitative approach using cross section data, this study uses multiple linear regression analysis. From this study, it was found that household income, nominal PKH, number of family members, amount of savings, and value of productive assets simultaneously had a significant effect on household consumption variables. The variable number of family members has the largest contribution in increasing household consumption.